2013
DOI: 10.1186/1743-422x-10-111
|View full text |Cite
|
Sign up to set email alerts
|

The tree shrew provides a useful alternative model for the study of influenza H1N1 virus

Abstract: BackgroundThe influenza pandemics have resulted in significant morbidity and mortality worldwide. Animal models are useful in the study of influenza virus pathogenesis. Because of various limitations in current laboratory animal models, it is essential to develop new alternative animal models for influenza virus research aimed at understanding the viral and host factors that contribute to virus infection in human.MethodWe investigated the replicative efficiency of influenza H1N1 virus (classic strain (Influenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 36 publications
1
46
0
Order By: Relevance
“…Therefore, it is being developed to be an experimental animal that could be an alternative to primates in biomedical research due to its unique characteristics 16 . In fact, tree shrew has been used for several animal models of virus infections, including hepatitis B 17 , influenza virus [18][19][20] , and Zika virus 21 . However, Tupaia model of high pathogenic viruses has not been reported yet, including SARS-CoV-2.…”
mentioning
confidence: 99%
“…Therefore, it is being developed to be an experimental animal that could be an alternative to primates in biomedical research due to its unique characteristics 16 . In fact, tree shrew has been used for several animal models of virus infections, including hepatitis B 17 , influenza virus [18][19][20] , and Zika virus 21 . However, Tupaia model of high pathogenic viruses has not been reported yet, including SARS-CoV-2.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that H1N1 and H9N2 influenza viruses replicate in the upper respiratory tract of tree shrews, which showed moderate respiratory symptoms and pathological signs (Yang et al, 2013;Li et al, 2018). Furthermore, while our manuscript was in preparation, Sanada and colleagues documented the pathogenicity of H5N1 and H7N9 IAVs in tree shrews (Sanada et al, 2019).…”
Section: Discussionmentioning
confidence: 63%
“…Yang and his colleagues demonstrated that H1N1 and H9N2 influenza viruses replicate in the upper respiratory tract of tree shrews, and exhibited moderate respiratory symptoms and pathological signs (Yang et al, 2013;Li et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Chinese tree shrew has been widely used to establish human disease models, such as virus infection (Yang et al, ), breast tumor (Xia et al, ), nonalcoholic fatty liver (Zhang et al, ), acute hyperuricemia (Tang et al, ), depression (Wang et al, ), Alzheimer's Disease (Fan et al, ), and so on. Findings suggest that cerebellar morphology in tree shrews more closely resembles that of primates than it does rodents (Sillitoe, Malz, Rockland, & Hawkes, ).…”
Section: Introductionmentioning
confidence: 99%